MicroRNAs won the Nobel Prize. Now, can extracellular vesicles help them become drugs? - Vanessa YiRan Li; Nicole Rosas; Sharon Fleischer; Gordana Vunjak-Novakovic; Ke Cheng (Extracellular Vesicle)
The 2024 Nobel Prize recognized microRNAs (miRNAs) as transformative regulators of gene expression. However, their clinical potential has been constrained by instability and delivery challenges. Extracellular vesicles (EVs), as natural carriers of miRNAs, address these limitations by protecting miRNAs from degradation and enabling their precise targeting. As such, harnessing EVs for miRNA delivery has the potential to redefine therapeutic approaches and offer innovative strategies to tackle the most challenging diseases of the 21st century. In this perspective, we examine the advantages and hurdles of EV-mediated miRNA delivery, from state-of-the-art research to its path toward commercialization. This article aims to inspire readers with the promise of EVs and miRNAs as revolutionary tools for future medicine.